PKM sport massage klub bolabasket flying wheel Makassar - Etno Setyagraha; Sulaeman Sulaeman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The way to reduce levels of lactic acid after exercising is by doing sports massage that functions as a stretch after exercising. Sport massage is one type of health massage specifically given to healthy people, especially sportsmen. This massage prioritizes the effect of blood circulation. Sport massage or sports massage is a way of massage using the hands massaged on the muscles of the body. Sports massage helps the circulation of blood and fluids in the body when it is done by rubbing, massaging and beating on the skin and muscles properly. In addition, sports massage relaxes the mind and body mentally. So many sports massage uses as science for sportsmen. Sport massage needs to be done to prevent injury and improve athlete's performance. The method used in this activity was lecture and question and answer and field practice carried out for three days. This activity is very useful for trainers, coaches, and masseurs and athletes because it is able to provide a sense of comfort and relaxation to participants. The participants realized that this activity was able to provide additional knowledge about sports massage. Suggestions given with this activity, Conduct similar socialization and training to Trainers, Guides, and Masseurs and athletes at basketball clubs in the City and District of South Sulawesi. The existence of the continuity of this community partnership program so that the Trainers, Guides, and masseur and athletes can really practice Sport Massage skills.